DIVERSITY OF GROUPER FISH (SERRANIDAE) IN COASTAL ZONE WATERS FROM DA NANG TO BINH THUAN - Quang, Vo Van (Vietnam Journal of Marine Science and Technology, 2019)
Based on surveys in 2014 and 2015, the species composition of groupers (Serranidae) caught in coastal areas from Da Nang to Binh Thuan is quite diverse with 38 species belonging to 7 genera. A collection of published works and these surveys (2014–2015) have showed that this sea area has 58 species belonging to 11 genera of family Serranidae; genus Epinephelus has been the most diverse one with 35 species. In which Khanh Hoa waters have the highest number of species of grouper with 45 species, followed by Binh Thuan with 25 species. The species of grouper from Da Nang to Binh Thuan coastal waters occupy 80.6% compared to the component species of grouper in Vietnam’s waters (72 species) and 46% of species of grouper in the Bien Dong (126 species). Groupers of Khanh Hoa waters are also more diverse compared with those in coral reef of Vietnam and coastal zone of North Central areas. The species composition of groupers (Serranidae) from Da Nang to Binh Thuan coastal zones has the association with six areas, including Andaman Sea (Thailand), coral reef of Vietnam, coral reef of Truong Sa archipelago, Quang Ninh - Thua Thien-Hue provinces, Hong Kong and Taiwan waters. In which similarity coefﬁcient is highest with Hong Kong and Quang Ninh - Thua Thien-Hue provinces. However, it is lowest with coral reef of Truong Sa archipelago.